PRODUCTION OF DIPLOID AND AMPHIDIPLOID INTERSPECIFIC HYBRIDS OF EGGPLANT AND SOLANUM TORVUM, AND POLLEN FERTILITY - S. Çürük; A. Dayan (Journal of Animal and Plant Sciences, 2018)
Eggplant (Solanum melongena L.) is susceptible to several pathogens and pests. However, Solanum torvum is resistant to Verticillium, bacterial wilts, root-knot nematode and some mycoplasmas. Sterile interspecific hybrids have been obtained from sexual or somatic hybridization studies of these species. The objective of this study is identifying a protocol that allows production a large number of interspecific hybrid plants between S. melongena and S. torvum by using in vitro embryo rescue and increasing the fertility by chromosome doubling to overcome the interspecific incompatibility problem. Seventy-seven interspecific hybrid genotypes from eggplant cultivar Faselis F × S. torvum crossing were 1 produced by in vitro embryo rescue from the seeds or underdeveloped ovules. Pollen viability and germination of the 50 interspecific hybrid genotypes were examined. The lowest and highest pollen viabilities in interspecific hybrid genotypes were 0.0% and 11.11%, respectively. The in vitro pollen germination of interspecific hybrids was by 0.0-1.36%. However, there was no fruit setting when the interspecific hybrid genotypes were backcrossed as a female with the parental species. The amphidiploid plants of some interspecific hybrid genotypes were obtained by 0.03% colchicine application. The pollen viability and germination percentages of the amphidiploid genotype were 11.57 and 9.43 fold of its diploid origin genotype, respectively. 1998). Consequently, it could be stated that the
Keywords: Amphidiploid; Interspecific Hybridization Barrier; Solanum melongena.